SUMBER DAYA MANUSIA INDONESIA MENGHADAPI ERA GLOBALISASI EKONOMI DITINJAU DARI SEGI PEMERATAAN - Kertopati, Ton (Universitas Prof. Dr. Moestopo (Beragama), 2004)
Most Indonesians would agree that the Indonesian enterprises should definitely play a more efficient role in the global economy. However, the argument that insist on the quality of human resources. Even if the government was willing to commit to a comprehensive programs. .While attempt to improve educational programs through internal restructuringmay be a valid concept. The present culture in government means it is toimplement reforms successfully.The willingness and the capacity to approach the capacity of human resourcesfor change to face _gn economical global problems